Hydrodeoxygenation of Bio-Derived Phenol to Cyclohexane Fuel Catalyzed by Bifunctional Mesoporous Organic–Inorganic Hybrids - Mo, Liuye; Yu, Wanjin; Cai, Huangju; Lou, Hui; Zheng, Xiaoming (Frontiers in Chemistry, 2018)
In this work, mesoporous silica materials SBA-15 functionalized with propyl/phenyl-sulfonic acid group were synthesized and loaded with Pt to form bifunctional catalysts. SAXRD, WAXRD, N2 adsorption-desorption, TEM techniques were used to characterize the above bifunctional catalysts. These bifunctional catalysts were applied to the reaction of hydrodeoxygenation (HDO) of bio-derived phenol (PhOH) to produce cyclohexane fuel and showed very good catalytic performances. There were strong synergies between the metal sites and the acid sites on the bifunctional catalysts. This reaction of phenol HDO provides a model system for the catalytic upgrading of biomass-derived fuel.